The Evaluation of a Modified Dufourmentel Flap after S-Type Excision for Pilonidal Sinus Disease - Murat Yildar; Faruk Cavdar; Mehmet Kamil Yildiz (The Scientific World Journal)
Purpose. The use of an S-type oblique excision with a bilateral gluteus maximus advancement flap has recently been described for the surgical treatment of sacrococcygeal pilonidal sinus (SPS). Its use in wide lesions has been limited due to the need for a full-thickness flap. We describe the use of an S-type oblique incision together with the Dufourmentel flap in wide lesions. Method. Twenty-one patients were treated using a technique including an S-shaped oblique excision of the sinus tract and a broad-pedicled full-thickness flap resembling a Dufourmentel flap to close the defect. Results. Of the 21 patients, 19 (90.5%) were male and 2 (9.5%) were female. Their mean age was (range 15–36) years. The mean follow-up period was (range 6–23) months. The postoperative complication rate was 4.8% (one patient), and recurrence was seen in one patient (4.8%). The mean return-to-work time was (range 10–18) days. None of the patients reported dissatisfaction with the cosmetic results. Conclusions. This new technique achieved low morbidity and recurrence rates. We anticipate that this will become an important technique in the surgical treatment of SPS if the observed success is confirmed by randomized prospective trials.